Key factors in supporting adolescents to achieve high self-esteem and a positive body image: A qualitative community-based study - Eva Artigues-Barberà; Glòria Tort-Nasarre; Mercè Pollina-Pocallet; Yvonne Ferrer Suquet; Aleix Ayats Pallés; Olívia Guasch Niubó; Marta Ortega-Bravo; Ester García-Martínez (PLoS ONE, 2025)
Introduction Body dissatisfaction can be affect adolescents’ mental health, leading to issues with body weight control, low self-esteem, and poor school performance. Methods A total of 24 interviews with adolescents, parents, and teachers in Spain were conducted for this study. The study aimed to explore and compare the views of adolescents, parents, and teachers regarding interventions to improve self-esteem and positive body image in school-aged adolescents. A generic qualitative study design with purposive sampling was used, and the data was thematically analyzed. Results Key barriers identified included lack of family communication, unfavourable family environments, and insufficient training. Social media and gender stereotypes, along with social rejection, were major challenges for adolescents. Facilitators included family involvement and using role models as a strategy. Proposed interventions focused on individual and group recreational activities starting at an early age, engaging adolescents in activities of interest, and promoting collaboration with families. Conclusion This study identified barriers and facilitators proposing multi-level interventions that engage adolescents, families, educational institutions, and the community. Strengthening facilitators and reducing barriers should guide future public health policies. Public contribution These findings may be useful for developing multilevel interventions aimed at improving body image and self-esteem, which could, in turn, prevent and reduce the severity of clinical disorders during adolescence.